Reconstruction of the late Holocene climate variability from the summer monsoon dominated Bhagirathi valley, western Himalaya - Roy, Ipsita; Ranhotra, Parminder Singh; Tomar, Nidhi; Shekhar, Mayank; Agrawal, Shailesh; Bhattacharyya, Amalava; Kumar, Pankaj; Patil, Shiva Kumar; Sharma, Rajveer (My University, 2022)
This study presents a centennial to decadal scale late Holocene climate scenario from the Indian summer monsoon (ISM) dominated region of western Himalaya. The subsurface sediments analyzed for palynology, carbon isotope (δ13Corg) and magnetic susceptibility (χlf) were collected from the temperate and alpine meadows, respectively receiving high (low) and relatively low (high) amount of ISM (winter) precipitation. We could identify the dry and moist phases linked to respective weakening and strengthening of ISM. High frequency of steppe pollen (Ephedra, Amaranthaceae, Asteraceae, Brassicaceae) between 4.4 and 3.8 ka represented a dry phase, coeval to 4.2 ka global dry event. Subsequent low δ13C values and high pollen frequency of moist vegetation (Geraniaceae, Cyperaceae, Apiaceae, Ranunculaceae and pteridophytes) till ca. 0.9 ka suggested moist phase but with an intermittent dry episode ca. 2.9–2.5 ka, allowing rise of steppe taxa. Climate ameliorated ca. 1.8 ka and moist conditions further enhanced between 1.5 and 0.9 ka, corresponding to Medieval Warm Period. Sharp increase in δ13Corg values and steppe vegetation ca. 0.8 ka attributed to dryness that intensified between 0.6 and 0.2 ka and coincide with Little Ice Age (LIA) anomaly. The recorded dry (weak ISM) phases showed correspondence with the low solar irradiance and supported the teleconnection with north Atlantic circulations. Palynological data from both the valleys complement each other throughout late Holocene time. However, the valleys showed temporal inconsistency in their aridity peaks during LIA phase. This indicates response variability of the two physiographically different sites to summer and winter monsoon systems.
Keywords: 4.2 ka even; Medieval Warm Period; Little ice age; Palynology; Carbon Isotope; Magnetic Susceptibility